Evaluation of avoralstat, an oral kallikrein inhibitor, in a Phase 3 hereditary angioedema prophylaxis trial: The OPuS‐2 study. Issue 9 (17th June 2018) - Riedl, M. A.; Aygören‐Pürsün, E.; Baker, J.; Farkas, H.; Anderson, J.; Bernstein, J. A.; Bouillet, L.; Busse, P.; Manning, M.; Magerl, M.; Gompels, M.; Huissoon, A. P.; et al.
Abstract: Background: Effective inhibition of plasma kallikrein may have significant benefits for patients with hereditary angioedema due to deficiency of C1 inhibitor (C1‐INH‐HAE) by reducing the frequency of angioedema attacks. Avoralstat is a small molecule inhibitor of plasma kallikrein. This study (OPuS‐2) evaluated the efficacy and safety of prophylactic avoralstat 300 or 500 mg compared with placebo. Methods: OPuS‐2 was a Phase 3, multicenter, randomized, double‐blind, placebo‐controlled, parallel‐group study. Subjects were administered avoralstat 300 mg, avoralstat 500 mg, or placebo orally 3 times per day for 12 weeks. The primary efficacy endpoint was the angioedema attack rate based on adjudicator‐confirmed attacks. Results: A total of 110 subjects were randomized and dosed. The least squares (LS) mean attack rates per week were 0.589, 0.675, and 0.593 for subjects receiving avoralstat 500 mg, avoralstat 300 mg, and placebo, respectively. Overall, 1 subject in each of the avoralstat groups and no subjects in the placebo group were attack‐free during the 84‐day treatment period. The LS mean duration of all confirmed attacks was 25.4, 29.4, and 31.4 hours for the avoralstat 500 mg, avoralstat 300 mg, and placebo groups, respectively. Using the Angioedema Quality of Life Questionnaire (AE‐QoL), improved QoL was observed for the avoralstat 500 mg group compared with placebo. Avoralstat was generally safe and well tolerated. Conclusions: Although this study did not demonstrate efficacy of avoralstat in preventing angioedema attacks in C1‐INH‐HAE, it provided evidence of shortened angioedema episodes and improved QoL in the avoralstat 500 mg treatment group compared with placebo.